Udvidelse af dramatikerens kampzone - Thygesen, Mads (Peripeti, 2022)
The playwright’s expanded battlefield This essay examines some of the main ideas and visions that have formed the basis for the education of playwriting in Denmark. Thygesen describes the development of the national school of playwriting and shows how the curriculum and methodology relates to the expanded field of playwriting in Denmark and abroad.